2014
DOI: 10.1016/j.pharep.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of the efficacy and safety of biosimilar G-CSF and originator G-CSF in haematopoietic stem cell mobilization

Abstract: A biosimilar G-CSF (Zarzio(®)) demonstrated similar efficacy and safety as the reference originator G-CSF (Neupogen(®)) in hematopoietic stem cell mobilization in patients with haematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…In a recent published study [29], after administration of mobilizing regimens [primarily high-dose etoposide, high-dose Cy, intermediate-dose cytosine arabinoside (Ara-C) or ESHAP regimens], patients with MM, non-Hodgkin's lymphoma, Hodgkin's lymphoma or other diagnosis were randomly assigned to a standard daily 10 mg/kg dose of biosimilar G-CSF or originator G-CSF. Both groups had a median of one apheresis with a median time until first apheresis of 11 days.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent published study [29], after administration of mobilizing regimens [primarily high-dose etoposide, high-dose Cy, intermediate-dose cytosine arabinoside (Ara-C) or ESHAP regimens], patients with MM, non-Hodgkin's lymphoma, Hodgkin's lymphoma or other diagnosis were randomly assigned to a standard daily 10 mg/kg dose of biosimilar G-CSF or originator G-CSF. Both groups had a median of one apheresis with a median time until first apheresis of 11 days.…”
Section: Discussionmentioning
confidence: 99%
“… 32 . It has been reported that cytokine concentration influences properties of stem cells 37 and more mature cells 36 , we therefore assume in the model that feedback signals act on all mitotic cell compartments.…”
Section: Methods and Model Descriptionmentioning
confidence: 99%
“…Collectively, these studies have shown that there are no significant differences between biosimilar versus originator G‐CSF in the median number of CD34+ cells mobilized (frequency in peripheral blood or dose of apheresed CD34+ cells by body weight) or in the number of G‐CSF injections and leukapheresis procedures required to harvest the target CD34+ cell dose . Furthermore, the side effect profiles of biosimilar versus originator G‐CSF were comparable, with a similar incidence and severity of common AEs such as bone or muscle pain and headache and no severe or unexpected AEs.…”
Section: Clinical Experience With Biosimilar G‐csf In Stem Cell Mobilmentioning
confidence: 92%